Dietary vitamin D equilibrium in serum ameliorates direct bilirubin associated diabetes mellitus - Sharma, Kuldeepak; Zajc, Irena; Žiberna, Lovro (Chemico-biological interactions, 2021)
Diabetes mellitus (DM), a non-communicable endocrine disease that is marked by a differing degree of tolerance to insulin and dysfunction. The connection between diabetes and liver failure important to doctors in general practice diabetologists and hepatologists. DM is linked with an elevated risk of hepatic consequences and mortality of liver cirrhosis patients. DM may facilitate to insult the liver by inducing inflammation and fibrosis by elevating mitochondrial oxidative stress. The conventional liver function indices are bilirubin including Indirect Bilirubin (IBil), Direct Bilirubin (DBil), and Total Bilirubin (TBil). DBil, IBil, and TBil, have diverse clinical implications as the standard index of liver disorder. An elevated level of DBil may suggest damage to the hepatic cell whereas TBil is within the normal range. Thus, increased liver enzymes are correlated with hepatic insulin resistance in healthy subjects. Notably, a significant correlation between DBil levels and Insulin resistance risk could indicate a connection between liver dysfunction and diabetes mellitus risk. Thus, our primary goal via the current review to examine the impact of dietary vitamin D (VitD) in serum mediated risk reduction of insulin resistance and further incidence of DM through inflammatory liver associated high DBil. Therefore, modifying these inflammatory pathways may be a therapeutic alternative approach for diabetes treatment. •Diabetes mellitus may facilitate to injury the liver by inducing inflammation and fibrosis.•DBil, IBil, and TBil, have diverse clinical implications as the standard index of liver disorder.•Increased liver enzymes are correlated with hepatic insulin resistance in healthy subjects.